(untitled) (Semiárida, 2020)
In this work, the whole genera and specles of the Leguminosae family which grows spontaneously in the Province of La Pampa, Argentine, are Iisted; 89 taxons are recorded, belonging to 77 species, 34 genera and 3 subfamilies. Keys for genera and species identification are attached. The valid name, synonyms and popular name, of each taxon, are given; also the bibliography of the first citation, iconography, distribution and frecuency in La Pampa and a selecled examined herbarium specimen. A summary table with origin, numbers of endemic taxons, numbers of genera, species and taxons is attached. The native taxons, Acacia caven (Molina) Molina, var. caven, A. caven var dehiscens Burkart ex Ciaidella, Adesmia muricata (Jacq.) OC. var muricata, Bauhinia forficata Link subsp. prulnosa (Vogel) Fortunato & Wunderlin, Oesmanthus acuminatus Benth. y Erythrina crista-galli L. and the adventives, Genista monspessulana (L.) L. A. S. Johnson, Lotus corniculatus L., lo glaber MilI., Senna corymbosa (Lam.) Irwin & Barneby, Spartlum Junceum L., Sutherlandia frutescens (L.) R. Br., Trifolium pratense L. y Vicia sativa L. subsp. nigra (L.) Ehrhart, are recorder for first time for this province.